2023
DOI: 10.3389/fcimb.2023.1169119
|View full text |Cite
|
Sign up to set email alerts
|

Causal associations between human gut microbiota and cholelithiasis: a mendelian randomization study

Abstract: BackgroundThere was some evidence that gut microbiota was closely related to cholelithiasis, but the causal relationship between them remained unclear. In this study, we try to use Two-sample Mendelian randomization (MR) to clarify the potential causal relationship between gut microbiota and cholelithiasis.MethodsSummary Genome-Wide Association Studies (GWAS) statistical data for gut microbiota was obtained from MiBioGen, and the data of cholelithiasis was obtained from UK Biobank (UKB). Two-sample MR analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Gryaznova (Gryaznova et al 2021) et al found that the intestinal ora of UC patients, Butyrivibrio, whose relative abundance was signi cantly lower, which later demonstrated a negative correlation with the risk of developing UC. In other clinical studies, an increase in the number of Butyrivibrio may be positively associated with the development of certain diseases, such as cholelithiasis (Li et al 2023). Wang believes that the possible mechanism is that the metabolites produced by Butyrivibrio prevent the liver from synthesizing bile acids from cholesterol in the blood, which slows down the conversion of cholesterol to bile acids and raises blood cholesterol, leading to a higher risk of gallbladder stone formation, which need further experimental studies (Li, Ren et al 2023), suggesting that gut bacteria play a complex role in various diseases.…”
Section: Discussionmentioning
confidence: 92%
“…Gryaznova (Gryaznova et al 2021) et al found that the intestinal ora of UC patients, Butyrivibrio, whose relative abundance was signi cantly lower, which later demonstrated a negative correlation with the risk of developing UC. In other clinical studies, an increase in the number of Butyrivibrio may be positively associated with the development of certain diseases, such as cholelithiasis (Li et al 2023). Wang believes that the possible mechanism is that the metabolites produced by Butyrivibrio prevent the liver from synthesizing bile acids from cholesterol in the blood, which slows down the conversion of cholesterol to bile acids and raises blood cholesterol, leading to a higher risk of gallbladder stone formation, which need further experimental studies (Li, Ren et al 2023), suggesting that gut bacteria play a complex role in various diseases.…”
Section: Discussionmentioning
confidence: 92%
“…This type of biliary tract fistula is uncommon. The dilation of intrahepatic bile ducts disrupts a stable biliary environment, leading to recurrent biliary inflammation, dysbiosis of the biliary microecology, and the formation of bilirubin stones ( 18 , 19 ). Additionally, it may result in periductal portal hypertension and induce liver atrophy ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…A smaller sample size means lower statistical power, making it even more challenging to reach such stringent P-value thresholds. To capture a broader spectrum of significant associations and enhance the power of our MR analysis, we opted to utilize exposure data with a less stringent threshold of P<1×10^-5 to select our instrumental variables ( Li et al., 2023 ). This decision was based on balancing the statistical stringency and the practical necessity of identifying a sufficient number of instrumental variables for a robust MR analysis.…”
Section: Methodsmentioning
confidence: 99%